THE ROLE OF INTERIOR DESIGN IN HUMAN LIFE (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, interior design is of particular note in today's era, when the field of modern architecture and construction is rapidly growing. It has been suggested that design is a philosophical view of the progress of human transformation into a daily inherent need, and that this process affects them in ethics-aesthetics. In this case, it was thought about what is the problem of society and how design philosophy affects the development of the cultural consciousness of society. The concept of design in a broad sense is aimed at revealing the inclusion of people in all aspects of the world in which they live. Explaining the realization that the rise of culture is directly related to imitation that there is a philosophy of design at the heart of human emotional desire, this article, in addition to providing an overview of interior design, highlights its types, its importance in construction and its role in human life.